Single stage correction of bilateral tessier 4 cleft - S M Balaji (Wolters Kluwer Medknow Publications, 2017)
Tessier facial clefts are among the rarest facial clefts reported in literature and many contradicting issues have always been rising over the management and surgical approaches involved during the craniofacial cleft repair. Among the craniofacial clefts Tessier no. 4 is an extremely rare facial anomaly, and there are very few evidence which clearly describe the surgical approaches and techniques. Often these type of craniofacial clefts yield very poor surgical results, and they require multidisciplinary sequential corrective surgeries. This article presents a rare case of an 18-month-old baby with bilateral Tessier no. 4 clefts and its successful rehabilitation.